Estudios del valor agregado en la comercialización del cultivo de tomate (Lycopersicum esculentum)” - Macías Peralta, Anthony (2021)
Worldwide, the production of kidney tomato is distributed in the countries of China, India, the United States and Turkey, as the main producers, at the Latin American level, Brazil is the only country that is considered by the FAO, as an important producer of tomato . Horticultural products, such as tomatoes, undergo a series of physiological processes after being harvested. Particularly in the case of tomato, being this climacteric, there are a series of compositional changes and quality aspects, which, influenced by pre-harvest practices, temperature, humidity, light, post-harvest handling and even varietal aspects, can result in a variation in the duration of its post-harvest useful life or shelf life The tomato marketing process occurs through various informal sale mechanisms, due to the lack of organization, thus proving a low economic situation in the producer's income. One of the options to improve marketing channels would be given by the evaluation, analysis and recommendations of this research. Marketing is essential for the entire company, making products available to consumers, positioning itself in a good market, which at the same time increases sales and is reflected in profits. With a correct commercialization, the satisfaction of the consumers is reached directly in an effective way, at a good price and with an excellent product. The first type of commercialization is known by the name of direct distribution, so there are no intermediaries involved and it is generally used by companies that have their own offices in the place or destination of the final consumer, for this large capital is required, such as the transnationals.